Cerebral depression due to propylene glycol in a patient with chronic epilepsy–the value of the plasma osmolal gap in diagnosis. Issue 754 (August 1988) - Lolin, Y.; Francis, D. A.; Flanagan, R. J.; Little, P.; Lascelles, P. T.
Abstract : A case of propylene glycol poisoning is described in a 39 year old woman which resulted in her admission to hospital in status epilepticus. She had had a long-standing history of uncontrollable epilepsy. The diagnosis of propylene glycol poisoning resulted directly from the finding of a high plasma osmolal gap on admission. This finding would have been missed if later samples only had been analysed. Plasma osmolality and the osmolal gap should be considered first line investigations in patients presenting with metabolic acidosis and cerebral signs and symptoms. Since her discharge from hospital a year ago the patient has had no further seizures.